EFEKTIVITAS PRINSIP FIRST TO FILE PADA SISTEM PENDAFTARAN MEREK DALAM MELINDUNGI HAK MEREK - Raden Fajar Agung Kusumahwardhana (Jurnal Privat Law, 2023)
The purpose of writing this article aims is to find out how the effectiveness of the implementation of the First To File principle in the trademark registration system and what problems arise from the application of the First To File principle in protecting trademark rights in Indonesia.This research is descriptive analytical as a description of a situation, and provides data about a situation. Collecting data in this writing is done in literature by examining data consisting of primary legal material and secondary legal material, then the data is analyzed using normative-qualitative methods.The results of the writing of this article indicate that Law Number 21 of 1961 concerning Company Marks and Commercial Trademarks which adhere to the First To Use system has been replaced by Law Number 19 of 1992 concerning Trademarks which applies the First To File principle. The First To File principle in the trademark registration system provides more legal certainty because it appoints the first registrant as the legal owner of a mark if it has passed a series of mark registration and has a trademark certificate, but in its implementation there are problems with the absence of clear and firm norms related to the application of "equality in essence. "So as to open up opportunities for the emergence of popularity of Well-Known Mark. Keywords: Intellectual Property Rights; Trademark; First To File.